Computing Topics on Multiple Imputation in Big Identifiable Data Using R: An Application to Educational Research - Ferrão, Maria Eugénia (2020)
This article shows how to conduct multiple imputation in big identifiable data for educational research purposes. The R statistical package and procedures to handle missing data applied for the purpose of this study were “Bay-lorEdPsych” and “mi”. Firstly, we checked that every dataset rejected the null hypothesis for Missing Completely At Random (MCAR), using the function “LittleMCAR”. Simulated and real data analyses were conducted. Results sug-gest that the improvement of the quality of imputation requires alternative methods to be developed.